PENGARUH AUDIT TENURE, UKURAN PERUSAHAAN, SPESIALISASI AUDITOR DAN LEVERAGE TERHADAP KUALITAS AUDIT (STUDI PADA PERUSAHAAN INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017) - Rizkiani, Nadia Meida; Nurbaiti, Annisa (EDUTECH CONSULTANT, 2019)
In this study we will measure the audit tenure, company size, auditor specialization and leverage on audit quality in infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. In this study, the data used was obtained from the financial statements of each company. The population in this study are infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange. The technique used in the sample selection was purposive sampling and obtained as many as 36 companies with the research period, namely in 2013-2017. The method used for data analysis in this study is logistic regression analysis using SPSS version 25. The results of the study show that simultaneous audit tenure, company size, auditor specialization, and leverage positively influence audit quality. While partially the results show that audit tenure and leverage have no effect on audit quality. However, company size and auditor specialization have a positive influence on audit quality.